Réponses

2014-01-07T12:13:32+01:00
Bonjour
g(x) = x^3-3x-4

f(x) = (x^3-2x²)/(x²-1)   de la forme de u/v 
avec u = x^3+2x²   donc u '  = 3x²-4x    et v = (x²-1)   donc v ' = 2x
f ' (x) = (3x²-4x)(x²-1)-(x^3-2x²)(2x)/(x²-1)²
f ' (x) = (3x^4-3x²-4x^3+4x-2x^4+4x^3)/(x²-1)²
f '(x)  = (x^4-3x²+4x)/(x²-1)² = [ x ( x^3-3x-4)]/(x²-1)² 
f ' (x) = [ x * g(x)] / (x²-1)² 
Tableau variation
x       -oo                       ]-1 [                   0                    ]1[            2.20            +oo
g(x)          croissante       -2   décroiss.           décroiss.   -6  croiss    0   croiss.
f ' (x)       décroiss.                 croiss        0     croiss.           decroiss.
 f(x)          croiss.                   croiss.       0     décroiss.        décroiss      croiss.

f(x) = x+2+(x+2)/(x²-1)
 f(x) = [ x(x²-1)+2(x²-1)+x+2]/(x²-1)
 f(x) = (x^3-x+2x²-2+x+2)/(x²-1)
f(x) = (x^3-2x²)/(x²-1)   ce qu'il fallait démontrer